Learning Style Profile of Medical Education Students Udayana University Faculty Of Medicine - Dewi, Ni Kadek Ayu Tena Oktari; Sundariyati, I Gusti Ayu Harry; Sundariyati, I Gusti Ayu Harry; Ganesha, I Gde Haryo; Darmayani, I Gusti Ayu Sri; Darmayani, I Gusti Ayu Sri (E-Jurnal Medika Udayana; Vol 14 No 5 (2025): E-Jurnal Medika Udayana, 2025)
Learning style is the process of how an individual receives and processes information to make it easier to understand and to remember for a longer period. In implementing a learning process, each student uses a learning style that suits their character. There are various learning styles, namely visual (V), auditory (A), Read/Write (R), and kinesthetic (K), or more commonly known as VARK. This research is conducted with the aim of gaining a deeper understanding of the learning style profiles of medical education students at Udayana University's Faculty of Medicine. This study is a quantitative descriptive with a cross-sectional study approach. Sampling was conducted among medical students at Udayana University from the 2020, 2021, and 2022 cohorts who met the inclusion and exclusion criteria. The technique used for sample selection is total sampling, with the minimum sample size calculated using the Slovin formula. Data collection was done using the online VARK version (8.01) questionnaire. Based on the univariate analysis of the research, the majority of respondents, 369 (74.9%), showed a preference for unimodal learning styles, and a small portion displayed multimodal learning styles, totaling 122 (25.1%). The most commonly used learning style among students is kinesthetic, with 289 (59.3%) participants favoring it. Consequently, the predominant learning style used by medical students at the Faculty of Medicine, Udayana University, from the 2020, 2021, and 2022 cohorts is the kinesthetic learning style, which falls under the unimodal learning model.